Seksualitas Tubuh Perempuan dalam Film Biografi Tentang Bintang Porno Lovelace - Fatima Meutia Rachma; Dr. Hapsari Dwiningtyas, S.Sos, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The study titled “Sexuality of Woman’s Body in A Biography Movie About Porn Star Lovelace” aims to find out how a porn star voiced her passion and to investigate the male perspective in this film. This study uses Sara Mills’ discourse analysis to determine the dominance of the male voice in the biography film about a woman with the elements like character, focalization, fragmentation, and schemata. Theories about the male gaze by Laura Mulvey used to analyze the dominant male perspective in this film. In addition, the theory of woman's voice by Luce Irigaray become a supporting theory to analyze how a woman voiced her voice. Results from this study shows that this movie uses male perspective and make the lead woman as an object to be stared at by another character as well as audiences. But this movie also expressed woman’s voice in a way which not really seen or heard.